Analisis Pengaruh CAR, NPF, BOPO Terhadap ROA Pada Bank Syariah - WULANDARI, AISYAH RACHMAWATI PUJI, Basworo Dibyo, S.E, M.Si (2017)
This study aimed to analyze the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Operating Expenses to Operating Income (ROA) to Return on Assets (ROA) at Bank Syariah in 2011-2015. The population in this study using Bank Syariah in Indonesia 2011-2014.The study sample as many as 9 BankSyariah sample method used is purposive sampling is a sampling method that takes an object with certain criteria. The data analysis method used is multiple linear regression analysis and classical assumption test,whereas hypothesis testing using t test, F test, and the coefficient of determination(R^2). From the results of the analysis during the observation period t test results showed that the variable Capital Adequacy Ratio (CAR) partially no effect on Return On Assets (ROA) while the variable Non Performing Financing (NPF) and Operating Expenses to Operating Income (ROA) is partially significant effect on Return on Assets (ROA). The results of F test analysis found that the variable Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Operating Expenses to Operating Income (ROA) together - each having an significant to the Return of Assets (ROA). The results of the analysis coefficient of determination (R^2) obtained Adjusted Square (R^2) of 0.887, this shows that the ROA can be explained by the variable CAR, NPF, and ROA of 88.7%, while the remaining 11.3% is explained by factors - other factors beyond the variables studied. Keyword: CAR, NPF, BOPO, ROA